2022
DOI: 10.1155/2022/2132754
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cinnamaldehyde Enhances Growth Performance, Digestion, Immunity, and Lipid Metabolism in Juvenile Fat Greenling (Hexagrammos otakii)

Abstract: Fat greenling (Hexagrammos otakii) is a kind of economic fish that is widely consumed by human, and its intensive farming technology is making important progress. However, high-density farming may cause the occurrence of diseases in H. otakii. Cinnamaldehyde (CNE) is a new feed additive for aquatic animals and has a positive effect on disease resistance. In the study, dietary CNE was evaluated on the growth performance, digestion, immune response, and lipid metabolism of juvenile H. otakii ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In the case of cinnamaldehyde, despite the absence of differences in the growth of Nile tilapia ( Oreochromis niloticus ) when supplementing the diets with this active principle (1 and 2 mL/kg) reported by Amer et al. ( 71 ), many studies have demonstrated its potential in improving growth performance in different fish species, such as Nile tilapia, grass carp ( Ctenopharyngodon idella ), tongue sole ( Cynoglossus semilaevis ), and fat greenling ( Hexagrammos otakii ) ( 72 75 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of cinnamaldehyde, despite the absence of differences in the growth of Nile tilapia ( Oreochromis niloticus ) when supplementing the diets with this active principle (1 and 2 mL/kg) reported by Amer et al. ( 71 ), many studies have demonstrated its potential in improving growth performance in different fish species, such as Nile tilapia, grass carp ( Ctenopharyngodon idella ), tongue sole ( Cynoglossus semilaevis ), and fat greenling ( Hexagrammos otakii ) ( 72 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 20 ) when supplementing gilthead seabream diets with 0.1% and 0.15% of this additive during winter. While none of the aforementioned studies testing the effect of capsicum in fish diets described an amelioration of FCR ( 56 , 58 60 ), some of the works with black pepper or ginger and many of those with cinnamaldehyde supplementation did ( 63 , 65 , 66 , 68 , 70 , 72 , 74 , 75 ). Therefore, the decrease in FCR in fish fed the SPICY 0.1% diet might be partly attributed to the active principles of ginger and black pepper and to cinnamaldehyde or to the synergetic effect of the four spices present in the tested product.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative real- time PCR analysis was conducted based on the study of Zhou et al. ( 28 ). In brief, RNA was extract ed from the intestinal tract of H. otakii at −80°C using the Trizol method ( 29 ).…”
Section: Methodsmentioning
confidence: 99%